Practical problems and breakthrough approach in cultivating innovative talent in public health and preventive medicine under the new medical sciences - Yue ZHANG; Rongbin YU; Jianming WANG; Yanshuang ZHAO; Ying LIU (Zhongguo gonggong weisheng)
Constructing a novel training model for innovative talent in public health and preventive medicine that integrates theory and practice has become a crucial aspect of medical education in China. Currently, public health and preventive medicine education in China faces challenges such as the difficulty of multidisciplinary integration across subjects and curricula, the struggle to reconcile teaching and research, and the lack of an optimized talent cultivation model. Therefore, this article outlines the current challenges and desired goals of cultivating innovative public health and preventive medicine talent while exploring potential breakthroughs under the "New Medical Science" initiative. The article discusses strategies including integrated development of disciplines and specialties, leading overall disciplinary development with first-class disciplines, balancing localized and internationalized approaches to education, and reconstructing the educational ecosystem under autonomous school management.